3D Gaze Estimation and Interaction to Stereo Display - Kwon, Yong-Moo; Jeon, Kyeong-Won; Ki, Jeongseok; Shahab, Qonita M.; Jo, Sangwoo; Kim, Sung-Kyu (International Journal of Virtual Reality, 2006)
There are several researches on 2D gaze tracking techniques to the 2D screen for the Human-Computer Interaction. However, the researches for the gaze-based interaction to the stereo images or 3D contents are not reported. The stereo display techniques are emerging now for the reality service. Moreover, the 3D interaction techniques are needed in the 3D contents service environments. This paper presents 3D gaze estimation technique and its application to gaze-based interaction in the parallax barrier stereo display